Options and Guidance for the Development of Baselines - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
Developed under the auspices of the Partnership for Market Readiness (PMR) and with advice and input from its Baselines Working Group, this document offers guidance and options for the development of emissions baselines, a key component for assessing the emission reductions in in both market and non-market based mechanisms. In the context of this document, a baseline refers to a scenario that describes expected or desired greenhouse gas emissions levels and that can be used as a basis for determining the amount of emissions reductions achieved as the result of a crediting, trading, or other mechanism. This document is divided into two parts. Part one (sections two and three) presents the context for emissions baselines, introduces key concepts and terms, and describes principles, considerations, and potential trade-offs that can inform decisions in the development of robust and transparent baselines. Part two provides a step-by-step description of how guidance users , a term we use here for those using this guidance, can develop baselines. Part two begins with a brief description of options for baseline development and approval, and proceeds in six further sections (5-10) to present options to define and update baselines. In the future, this document will be supplemented by additional documents illustrating how the guidance presented here can be applied to specific market or non-market mechanisms involving a variety of economic sectors and GHG emission sources. Finally, this document is intended to be dynamic. Over time, as experience is gained and consensus emerges on best practices, this document may evolve to provide more specific guidelines, where and as appropriate.